BIOM-42. IMMUNOHISTOCHEMICAL ASSESSMENT OF MEMBRANOUS SOMATOSTATIN TYPE 2A RECEPTOR (SST2A) EXPRESSION ACROSS HIGH-RISK PEDIATRIC CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (12th November 2021) - Lazow, Margot; Trout, Andrew; Fuller, Christine; Reuss, Jaime; Turpin, Brian; Stanek, Joseph; Szabo, Sara; Salloum, Ralph
Abstract: INTRODUCTION: 77 Lu-DOTATATE, a radionuclide therapy which binds SST2A, has demonstrated efficacy in neuroendocrine tumors and evidence of CNS penetration, supporting potential expansion within pediatric neuro-oncology. Understanding the prevalence of SST2A expression across pediatric CNS tumors is essential to identify patients who may benefit from somatostatin receptor-targeted therapy and to further elucidate the oncogenic role of SST2A. METHODS: SST2A immunohistochemistry (IHC) was performed on tumor specimens and interpreted by two experienced pathologists (blinded), utilizing semi-quantitative scoring of membranous expression within viable tumor. Immunoreactive cell percentage was visually scored as 0 (none), 1 (< 10%), 2 (10-50%), 3 (51-80%), or 4 (>80%). Staining intensity was scored as 0 (none), 1 (weak), 2 (moderate), or 3 (strong). Combined scores for each specimen were calculated by multiplying percent immunoreactivity and staining intensity values (range=0-12). RESULTS: A total of 117 tumor samples from 113 patients were analyzed. Significant differences in SST2A IHC scores were observed across histopathologic diagnoses, with consistently high scores in medulloblastoma (mean±SD=7.6±3.6 [n=36]) and meningioma (5.7±3.4 [n=15]), compared to minimal or absent expression in ATRT (0.3±0.6 [n=3]), ETMR (1.0±0 [n=3]), ependymoma (grades I-III; 0.2±0.7 [n=26]), and high-grade glioma (grades III-IV; 0.4±0.7 [n=22]). Pineoblastoma (3.8±1.5 [n=4]) and other embryonal tumors (2.3±3.8 [n=8]) exhibited intermediate, variable expression. Among expressors, there was no association between SST2A IHC score and patient age, sex, presence of metastases, likelihood of relapse, or prior treatment. In a subset of paired primary and recurrent specimens from 3 patients, SST2A IHC scores remained largely unchanged. Among medulloblastomas, SST2A IHC scores were higher in non-SHH (8.6±3.2) than SHH (5.0±3.3) molecular subgroups (p=0.033). CONCLUSIONS: High membranous SST2A expression was demonstrated in medulloblastoma, meningioma, and some rarer embryonal tumors with potential diagnostic, biologic, and therapeutic implications. Somatostatin receptor-targeted therapy such as 177 Lu-DOTATATE deserves further investigation in these highly SST2A-expressing pediatric CNS tumors.